Endometriosis in the Mouse: Challenges and Progress Toward a ‘Best Fit’ Murine Model - Burns, Katherine A.; Pearson, Amelia M.; Slack, Jessica L.; Por, Elaine D.; Scribner, Alicia N.; Eti, Nazmin A.; Burney, Richard O. (Frontiers in Physiology, 2022)
Endometriosis is a prevalent gynecologic condition associated with pelvic pain and infertility characterized by the implantation and growth of endometrial tissue displaced into the pelvis via retrograde menstruation. The mouse is a molecularly well-annotated and cost-efficient species for modeling human disease in the therapeutic discovery pipeline. However, as a non-menstrual species with a closed tubo-ovarian junction, the mouse poses inherent challenges as a preclinical model for endometriosis research. Over the past three decades, numerous murine models of endometriosis have been described with varying degrees of fidelity in recapitulating the essential pathophysiologic features of the human disease. We conducted a search of the peer-reviewed literature to identify publications describing preclinical research using a murine model of endometriosis. Each model was reviewed according to a panel of ideal model parameters founded on the current understanding of endometriosis pathophysiology. Evaluated parameters included method of transplantation, cycle phase and type of tissue transplanted, recipient immune/ovarian status, iterative schedule of transplantation. and option for longitudinal lesion assessment. Though challenges remain, more recent models have incorporated innovative technical approaches such as in vivo fluorescence imaging and novel hormonal preparations to overcome the unique challenges posed by murine anatomy and physiology. These models offer significant advantages in lesion development and readout toward a high-fidelity mouse model for translational research in endometriosis.